Chronic Synthetic Marijuana Use: A Case of First-Onset Seizures as a Withdrawal Symptom - Amber N. Edinoff; Prithvi Doppalapudi; Juliana M. Fort (Health Psychology Research)
A 44-year-old male with no known past medical history but a known history of daily synthetic marijuana use presented to the emergency department after two witnessed seizures. The patient was admitted to the neurology service, where he was worked up with an MRI with epilepsy protocol and an EEG. During admission, the patient was admitted to daily synthetic marijuana use. He did note that he had started to decrease the amount of mojo he used daily in an attempt to stop. His last use was at 9 am the day of his admission. He was trying to decrease his use; his girlfriend of difficulty word-finding noted periods. Synthetic marijuana (SM) or "mojo" use has been increasing in the past decade for two reasons; It is considered an herbal product and has been legal. A withdrawal syndrome of SM use has been characterized chiefly as tachycardia, irritation, anxiety, and mood swings. These withdrawal symptoms are usually seen with chronic use. Some early results in the literature also show that SM use can lead to functional and structural neuronal changes. This manuscript discusses a case of a first on-set seizure as a possible withdrawal symptom in chronic SM use.